2022
DOI: 10.1088/2515-7620/ac6381
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative verification of the turbulence barrier effect during heavy haze pollution events

Abstract: Under calm and steady weather conditions with low wind speeds, turbulent intermittency frequently occurs in the atmospheric boundary layer (ABL), which can significantly weaken the turbulent diffusion of matter and energy between the surface and atmosphere. The turbulence barrier effect is defined as the phenomenon in which turbulence may disappear at certain heights, and during periods of heavy haze, creating what can seem like a barrier layer that hinders vertical transmissions. Although the turbulence barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Ren et al. (2022) documented that the rapid accumulation of pollutants is related to weak turbulence during heavy haze. The knowledge of the transition of turbulence regimes can be directly used to constrain the validity range of Monin‐Obukhov similarity theory in numerical simulations for weather and pollutants dispersion.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ren et al. (2022) documented that the rapid accumulation of pollutants is related to weak turbulence during heavy haze. The knowledge of the transition of turbulence regimes can be directly used to constrain the validity range of Monin‐Obukhov similarity theory in numerical simulations for weather and pollutants dispersion.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For instance, Sandu et al (2013) reported that the representation of stably stratified turbulence in numerical weather prediction models remains a challenge, especially for the weak turbulence regime. Ren et al (2022) documented that the rapid accumulation of pollutants is related to weak turbulence during heavy haze. The knowledge of the transition of turbulence regimes can be directly used to constrain the validity range of Monin-Obukhov similarity theory in numerical simulations for weather and pollutants dispersion.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Inversion layer frequently develops in winter and traps PM 2.5 emitted from the ground within a shallow layer. According to the "barrier effect" theory (Ren et al, 2021), turbulence disappears at some heights and laminar flow develops during heavily polluted periods, which serves as a barrier layer impeding vertical turbulence transport. In the presence of the LLJs, turbulence bursts produced by aloft wind shear enhance vertical mixing, break the decoupled ABL structure, and rebuild the heat/momentum/material exchange between different heights.…”
Section: Vertical Transport Of Mineral Dustmentioning
confidence: 99%